2020
DOI: 10.18632/oncotarget.27585
|View full text |Cite|
|
Sign up to set email alerts
|

Immunotherapy of ovarian cancer with a monoclonal antibody specific for the extracellular domain of anti-Müllerian hormone receptor II

Abstract: Epithelial ovarian carcinoma (EOC) is the most prevalent and lethal form of ovarian cancer. The low five-year overall survival after EOC diagnosis indicates an urgent need for more effective ways to control this disease. Anti-Müllerian hormone receptor 2 (AMHR2) is an ovarian protein overexpressed in the majority of human EOCs. We have previously found that vaccination against the ovarian-specific extracellular domain of AMHR2 (AMHR2-ED) significantly inhibits growth of murine EOCs through an IgG-mediated mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…While efforts have been made to model the structure of AMH bound to AMHR2, the exact fold of the receptor-and ligand-binding interface remained unclear (19,20,28,29). Furthermore, some of these studies have used these models in an attempt to characterize antibodies designed to bind AMHR2, specifically for use in targeted cancer cells expressing high levels of AMHR2 (19,28). Interestingly, all models of AMHR2 were inaccurate and unable to predict the fold of the finger 1 loop extension in the receptor.…”
Section: Discussionmentioning
confidence: 99%
“…While efforts have been made to model the structure of AMH bound to AMHR2, the exact fold of the receptor-and ligand-binding interface remained unclear (19,20,28,29). Furthermore, some of these studies have used these models in an attempt to characterize antibodies designed to bind AMHR2, specifically for use in targeted cancer cells expressing high levels of AMHR2 (19,28). Interestingly, all models of AMHR2 were inaccurate and unable to predict the fold of the finger 1 loop extension in the receptor.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that anti-Müllerian hormone receptor type II (AMHR2) is expressed in approximately 92% of primary EOCs, 78% of borderline malignancies, 77%–86% of non-EOC ovarian tumors, and 56% of malignant ascites from grades III-IV ovarian cancers [ 9 10 11 12 ]. AMHR2 is a serine/threonine kinase receptor homologous to type II receptors of the transforming growth factor-beta superfamily [ 13 ].…”
Section: Introductionmentioning
confidence: 99%